I Do It, but I Decide With Whom - Pulido, Cristina M.; Vidu, Ana; Racionero-Plaza, Sandra; Puigvert, Lídia (Frontiers in Psychology, 2021)
Social interactions and communication shape men’s and women’s desires and preferences. While it is true that some men have modified their behavior due to feminist women, the same happened with some women, who changed attraction patterns thanks to New Alternative Masculinities (NAM). This article examines the latter, focusing on social interactions mediated by language, as a crucial element to impact and change people’s desires. For this purpose, six autobiographical interviews were conducted with women aged 19-39, from two different countries and continents, paying attention to the narratives of their sexual-affective relationships. Using the communicative methodology, interactions have been analyzed from verbal and non-verbal communication, based on the consequences of the actions rather than intentionality. The results of this study show how dialogic communicative acts with NAMs influenced some women who first defended or justified actions of male perpetrators, to later prefer to support female survivors against their perpetrators. Analysis reveals that communicative acts grounded in such language that enacted NAM’s desire for women of solidarity have shaped some women’s memories of relationships with Dominant Traditional Masculinities and, ultimately, contributed to change their attraction and election patterns.